The flux of organic matter through a peatland ecosystem: The role of cellulose, lignin, and their control of the ecosystem oxidation state. Issue 7 (11th July 2017) - Worrall, Fred; Moody, Catherine S.; Clay, Gareth D.; Burt, Tim P.; Rose, Rob
Abstract: This study used thermogravimetric analysis (TGA) to study the transit of organic C through a peatland ecosystem. The biomass, litter, peat soil profile, particulate organic matter (POM), and dissolved organic matter (DOM) fluxes were sampled from the Moor House National Nature Reserve, a peat‐covered catchment in northern England where both the dry matter and carbon budget for the catchment were known. The study showed that although TGA traces showed distinct differences between organic matter reservoirs and fluxes, the traces could not readily be associated with particular functionalities or elemental properties. The TGA trace shows that polysaccharides are preferentially removed by humification and degradation with residual peat being dominated by lignin compositions. The DOM is derived from the degradation of lignin while the POM is derived from erosion of the peat profile. The carbon lost as gases (CO2 and CH4 ) was estimated to be composed of 92 to 95% polysaccharide carbon. The composition of the organic matter lost from the peat ecosystem means that the oxidative ratio (OR) of the ecosystem experienced by the atmosphere was between 0.96 and 0.99: currently, the Intergovernmental Panel on Climate Change uses an OR value of 1.1 for all ecosystems. Key Points: Processing of organic matter through a peatland preferentially removes carbohydrates and retains lignin Dissolved organic matter (DOM) from peatlands is derived from processing of lignin and not carbohydrates The atmosphere above the peatland experiences an oxidative ratio (OR) less than 1 and not 1.1 as assumed globally